A mutation of EYA1 gene in a Chinese Han family with Branchio-Oto syndrome. Issue 25 (25th June 2021) - Han, Rui; Xia, Yan; Liu, Zhijuan; Wu, Shuang; Ye, Erdengqieqieke; Duan, Ling; Ding, Jianbing; La, Xiaolin
Abstract : Abstract: Branchio-Oto (BO) syndrome is one of the common syndromic forms of hearing loss. In this study, we aimed to characterize the clinical and genetic features of BO syndrome in a Chinese deaf family. The proposita in this study was a 29-years-old Chinese female with hearing loss, microtia, anterior concave auricle, and right branchial fistula. The family members agreed to undergo clinical examination. We collected blood samples from 7 family members, including 4 affected by the syndrome. Genomic DNA was extracted and subjected to Sanger sequencing. In addition, bioinformatics software SWISS MODEL was used to predict the protein encoded by EYA transcriptional coactivator and phosphatase 1 ( EYA1 ) gene. Intra-familial consistency can be observed in the clinical phenotypes of BO syndrome in this family. EYA1 c.1627C>T (p.Gln543Ter) mutation was identified as the pathogenic cause in this family. This study reports a mutation associated with BO syndrome in a Chinese Han family. We highlight the utility of genetic testing in the diagnosis of BO syndrome. Thus, we believe that this report would provide a basis for the diagnosis of similar diseases in the future.